2006
DOI: 10.1039/b608904f
|View full text |Cite
|
Sign up to set email alerts
|

The advantage of using carbon nanotubes compared with edge plane pyrolytic graphite as an electrode material for oxidase-based biosensors

Abstract: Carbon nanotubes (CNTs) are promising materials for use in amperometric biosensors. The defect sites at their ends, and on their sidewalls, are considered to be edge plane-like defects and show high electrocatalytic activity toward several biological molecules. However, electrocatalytic activity toward H(2)O(2) has not been compared among bamboo-structured CNTs (BCNTs), which have many defect sites; hollow-structured CNTs (HCNTs), which have few defect sites; edge plane pyrolytic graphite (EPG); and traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…The subtle electronic properties suggest that CNTs have the ability to promote electron-transfer reactions, when used as an electrode in chemical reactions [8,9]. Recent studies demonstrated that a CNT modified electrode could impart strong electrocatalytic activity to some important biomolecules [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The subtle electronic properties suggest that CNTs have the ability to promote electron-transfer reactions, when used as an electrode in chemical reactions [8,9]. Recent studies demonstrated that a CNT modified electrode could impart strong electrocatalytic activity to some important biomolecules [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The nonplatinum based H 2 O 2 electrooxidation catalysts include palladium, nickel cyclam, ruthenium, ruthenium-platinum alloys, iridium dioxide, single-walled carbon nanotubes and polypyrrole functionalized multiwalled-carbon nanotubes. 62,[225][226][227][228][229][230][231][232][233][234][235] Part of the catalyst research has been aimed at reducing the potential at which the H 2 O 2 is electrooxidized, that is, at better selectivity in the presence of electrooxidizable interferants. 236 H 2 O 2 has been typically electrooxidized on Pt about 600 mV vs SCE, where ascorbate, urate, and acetaminophen are also electrooxidized.…”
Section: Electrooxidation Of the H 2 O 2 Produced Upon Enzyme-catalyzmentioning
confidence: 99%
“…Nano-materials that are applied to the sensors include a variety of materials such as nanowire [37][38][39][40], carbon nanotube [41][42][43][44], nano fiber [45][46][47][48][49], nano particles [50][51][52][53][54], metal nano-pattern and ion-channel material [41,55,56]. As many good reports on this study have been published, please refer to them for more information.…”
Section: Basic Principles and Research Trend Of Biosensorsmentioning
confidence: 98%